Permasalahan yang Dialami oleh Mahasiswa Calon Guru Biologi dalam Belajar Strategi Pembelajaran Biologi dan Cara Mengatasinya - Bowo Sugiharto; Aloysius Duran Corebima; Herawati Susilo; Ibrohim Ibrohim (Universitas Sebelas Maret, 2016)
Biology Learning Strategies is an important subject that is constitute the competence of biology teachers candidate student, particularly pedagogy competence. This study aims to describe the biology teachers candidate student’s learning strategy, problems encountered, and the chosen learning solution in Biology Learning Strategy subjects. This explorative survey conducted in March-April In 2016. The study involved 176 participants. The participants are students of 4th semester biology teacher candidates who have been to take a course Biology Learning Strategies. Data were collected using a semi-open and open questionnaire. Analysis of data using qualitative data analysis model of Miles and Huberman which includes data reduction, data presentation, and drawing conclusions and verification. The study concluded that most of students learn Biology Learning Strategies subject by understanding that as much as 54.1%, memorizing and understanding as much as 36.4%, just memorizing as much as 5.1%, and others as 45%. Problems experienced by students in learning Biology Learning Strategies subject include discomfort during a rowdy class, the ability to understand, lack of confidence when the practice is conducted, the ability to define a strategy or apply the material in the practice, as well as the difficulty to memorize. How to overcome the problems in learning Biology Learning Strategies subject quite diverse among others by asking questions, discussions with friends and the lecturer, relearn the material, looking for references from the book and internet and frequent teaching practice.